Performance of Corrosion Behavior of Commercial Magnesium Alloy Anode Electrode in Seawater-Powered Lamps - Rezza Ruzuqi; Eko Tavip Maryanto; Muhamad Ali Ulat; Dwi Rosalina; Ar Hanung Triyono; Siswanto Siswanto (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2024)
The development of environmentally friendly alternative technologies, such as seawater batteries, is increasingly important in addressing energy needs. This study aims to analyze the corrosion behavior of a magnesium alloy anode electrode used in seawater batteries with varying salinity levels. Five commercial anode electrode samples were prepared, each immersed in a salt solution with different concentrations: 14g, 16g, 18g, 20g, and 22g in 380 ml of distilled water. Potentiodynamic testing was conducted to measure the corrosion potential (Ecorr), corrosion current (Icorr), and corrosion rate. The results showed that an increase in salt concentration significantly increased the corrosion rate. The sample with the highest salt concentration (22g) produced a corrosion potential of 1.5419 Volts, a corrosion current of 0.0010 Amps/cm², and a corrosion rate of 12.5850 mm/year. These findings indicate that the corrosion rate increases with higher salinity. The study concludes that there is a positive correlation between salinity and corrosion rate, with future research expected to focus on additional treatments to improve electrode performance.